Regression of fibrosis by cilostazol in a rat model of thioacetamide-induced liver fibrosis: Up regulation of hepatic cAMP, and modulation of inflammatory, oxidative stress and apoptotic biomarkers - El Awdan, Sally A. (PLoS One, 2019)
In liver fibrosis, conversion of fibroblasts to profibrogenic myofibroblasts significantly drives the development of the disease. A crucial role of cyclic adenosine monophosphate (cAMP) in regulation of fibroblast function has been reported. Increase in cAMP levels has been found to decrease fibroblast proliferation, inhibit their conversion to myofibroblast, and stimulate their death. cAMP is generated by adenyl cyclase (AC), and degraded by cyclic nucleotide phosphodiesterase (PDE). In this study, the antifibrotic effect of a PDE inhibitor, cilostazol (Cilo), on a rat model of liver fibrosis induced by thioacetamide (TAA) was investigated. Four groups of rats were used; the first group received the vehicles and served as the normal control group, while liver fibrosis was induced in the other groups using (TAA, 200 mg/kg/biweekly for 8 successive weeks, ip). The last two groups were treated with Cilo (50 and 100 mg/kg/day, po, respectively). Induction of liver fibrosis in TAA-treated rats was observed as evidenced by the biochemical and histopathological findings. On the other hand, a potent antifibrotic effect was observed in the groups treated with Cilo, with preference to the higher dose. In these groups, a significant increase in the liver content of cAMP was demonstrated that was accompanied by reduction in the hepatic expression of key fibrogenic cytokines, growth factors, and inflammatory biomarkers, including interleukin-6, tumor necrosis factor-alpha, nuclear factor kappa B, and transforming growth factor-beta as compared to TAA group. Moreover, amelioration of TAA-induced oxidative stress and apoptosis in the liver has been observed. These findings reveal the antifibrotic effect of Cilo against TAA-induced liver fibrosis in rats, and suggest regulation of cAMP pathway, together with the modulation of oxidative stress, inflammation, and apoptosis as mechanistic cassette underlines this effect.